1975
DOI: 10.1017/s0021859600062365
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-environment interaction – a challenge for plant breeding

Abstract: Much has been written and said about genotype-environment (GE) interactions and the particular problems which they pose for plant breeders. It is not the purpose of this article to dwell upon every aspect of this story, but rather to discuss how these problems came to be recognized, to comment upon the various techniques which have been employed in seeking a solution to them and to suggest what developments might lie ahead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
4

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 65 publications
1
89
0
4
Order By: Relevance
“…Hill (1975 (Crossa et al, 1990 On the basis of our results, we concluded that the line x environment interaction for biomass dry matter yield in maize could essentially be due to differences in line earliness and lodging susceptibility (and to the different ability of the environments to reveal them), and to differences in environment rainfalls (and to the variable susceptibility of the lines to water stress).…”
Section: Factorial Regressionmentioning
confidence: 71%
“…Hill (1975 (Crossa et al, 1990 On the basis of our results, we concluded that the line x environment interaction for biomass dry matter yield in maize could essentially be due to differences in line earliness and lodging susceptibility (and to the different ability of the environments to reveal them), and to differences in environment rainfalls (and to the variable susceptibility of the lines to water stress).…”
Section: Factorial Regressionmentioning
confidence: 71%
“…While there is no comparable analysis of any other cross, the literature now contains many reports, too numerous to cite individually, of linear relationships between genotype x environment interactions and some 57 environmental index (see, for example, reviews by Freeman, 1973;Hill, 1975). There are many others, however, as was shown by Perkins and Jinks (I 968a, b, and 1973) with J'*Iicotiana rustica material, where the relationship is non-linear.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current example, the heterogeneity mean square was large enough to be significant when tested against the deviation mean square (Table 8). Thus, according to Perkins and Jinks (1968) and Hill (1975), the coefficients of the linear model have practical value, although the predictive value of regression is not the same for each genotype.…”
Section: Joint Regression Analysesmentioning
confidence: 99%
“…However, variance component analyses alone often do not provide a satisfactory explanation for GE interactions. Simply recognizing different genotypic responses to environmental stress does not distinguish between crossover and noncrossover interactions, and it is desirable to interpret, rather than correct, the GE component (Hill 1975;Baker 1988a;Baker 1988b). Consequently, a number of parametric methods have been developed to assist in the interpretation of GE interactions (Freeman 1973;Hill 1975;Westcott 1986) and to determine the level of adaptation of genotypes (Finlay and Wilkinson 1963).…”
mentioning
confidence: 99%